The Menstrual Cup Effect - Flamand, Iris (Student Undergraduate Research E-journal!, 2018)
This research is dedicated to comparative environmental impact analyses of menstrual products – tampons with and without applicator, sanitary pads, and menstrual cups – used in modern “Western” societies and using six indicators of environmental impact. Additionally, a menstrual waste scenario analysis, with increasing menstrual cup use as variable, is performed. Due to environmental concern, especially for waste, the research question and the survey were formed. All indicators showed lowest impact with menstrual cups. Besides, if menstrual cup-use sextupled, a waste reduction of 84% was calculated. Consumers and researchers must identify and adjust environmental impacts of everyday products, like menstrual products.